Analysis Of The Relationship Of Learning Results On Creative Products And Entrepreneurship With The Interest In Entrepreneurship Of Culinary Students Of Vocational School 1 Batusangkar - Cahyani, Bunga Gusti; Siregar, Juliana; Andriani, Cici; Insan, Ranggi Rahimul (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Abstract:The background of this research focuses on the importance of entrepreneurial skills in facing increasingly complex global economic challenges. In this context, entrepreneurship education is expected to encourage students to develop the interests and skills needed for entrepreneurship. The aim of the research is to analyze the relationship between learning outcomes and entrepreneurial interest in Class XI Culinary Arts students at SMK Negeri 1 Batusangkar.  This research method is quantitative correlational research. The research subjects were 33 SMK Negeri 1 Batusangkar. Data collection is carried out via gform. Data were analyzed descriptively and by regression test analysis. using the SPSS version 26 for Windows program. The results of the research show that the description of learning outcomes in the Creative Products and Entrepreneurship Subjects of Class XI Culinary Arts students at SMK Negeri 1 Batusangkar is in the low category.  The description of interest in entrepreneurship among Class XI Culinary Arts students at SMK Negeri 1 Batusangkar is in the low category. There is a significant positive relationship between learning outcomes and interest in entrepreneurship for Class XI Culinary Arts students at SMK Negeri 1 Batusangkar. The research concluded that there is a relationship between learning outcomes and students' entrepreneurial interest.